The use of ultrasound to assess giant cell arteritis: review of the current evidence and practical guide for the rheumatologist. (27th April 2017) - Monti, Sara; Floris, Alberto; Ponte, Cristina; Schmidt, Wolfgang A; Diamantopoulos, Andreas P; Pereira, Claudio; Piper, Jennifer; Luqmani, Raashid
Abstract: Colour duplex sonography (CDS) of temporal arteries and large vessels is an emerging diagnostic tool for GCA. CDS can detect wall oedema, known as a halo, throughout the length of the vessel and shows higher sensitivity compared with biopsy. Specificity reaches 100% in case of bilateral halos. A positive compression sign has been demonstrated to be a robust marker with excellent inter-observer agreement. The assessment of other large vessels, particularly the axillary arteries, is recognized to further increase the sensitivity and to reliably represent extra-cranial involvement in other areas. Nevertheless, CDS use is still not widespread in routine clinical practice and requires skilled sonographers. Moreover, its role in the follow-up of patients still needs to be defined. The aim of this review is to provide the current evidence and technical parameters to support the rheumatologist in the CDS evaluation of patients with suspected GCA.